(untitled) (Journal of Bangladesh Institute of Planners, 2015)
Transport accessibility is a very important criterion which influences rental value and housing preference of the tenants. This paper analyzes the relation between transport accessibility and house rental as well as the relative importance of transport accessibility indicators to the tenants for rental housing decision choice. This research analyzed data collected from 200 sample residents of rental housing from the middle-income areas of Dhaka city. This research found that transport accessibility is an important factor for the variation of house rental and there is a significant variation in the relative importance of different transport accessibility attributes to the tenants in Dhaka. Proximity to bus stop is the most important criterion for the tenants followed by the condition of front road, distance to major road, width of front road, distance to market and distance to the CBD. However, many households of middle-income bracket in Dhaka usually compromise their housing preference due to limited affordability. This study suggests for appropriate land use planning along with housing planning so that transport accessibility could be improved within the affordability level of the tenants. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 73-83